2014
DOI: 10.1155/2014/746298
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy Use in Bladder Cancer: A Survey of Current Practice and Opinions

Abstract: Objectives. Level 1 evidence supports the use of neoadjuvant chemotherapy (NAC) to improve overall survival in muscle invasive bladder cancer; however utilization rates remain low. The aims of our study were to determine factors associated with NAC use, to more clearly define reasons for low utilization, and to determine the current rate of NAC use among urologic oncologists. Materials and Methods. Active members of the Society for Urologic Oncology were provided a 20-question survey. Descriptive statistical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…It is in fact difficult to determine the true number of appropriate patients who should receive NAC. In a survey conducted of all active members of the Society for Urologic Oncology regarding their practice patterns and opinions regarding NAC, Cowan and colleagues [29] noted that urologic oncologists cite age, comorbidity, delay in surgery, and modest marginal benefit as the principle determinants to eschew NAC. Intriguingly, only 65% of responding urologic oncologists discussed NAC with 90% of their patients for whom RC was an option.…”
Section: Discussionmentioning
confidence: 99%
“…It is in fact difficult to determine the true number of appropriate patients who should receive NAC. In a survey conducted of all active members of the Society for Urologic Oncology regarding their practice patterns and opinions regarding NAC, Cowan and colleagues [29] noted that urologic oncologists cite age, comorbidity, delay in surgery, and modest marginal benefit as the principle determinants to eschew NAC. Intriguingly, only 65% of responding urologic oncologists discussed NAC with 90% of their patients for whom RC was an option.…”
Section: Discussionmentioning
confidence: 99%
“…When asked which factors influence nonadherence in the use of NAC in their practice (33.8% of responders), we found that the major concerns about the NAC recommendation is the delay in surgery and patient's comorbidity. Two other national surveys among US urologists reported similar worries in the utilization of NAC for MIBC [21,23]. The side effects of NAC are well known but do not seem to cause a delay in the subsequent RC.…”
Section: Mibc Gls Adherence (Q4)mentioning
confidence: 77%
“…Feifer et al [14] found a similar discrepancy with usage rates of 12 and 22% for NAC and AC respectively. More recent studies suggest an increase in NAC usage in the United States, while AC usage remains stable [15, 16]. Reasons commonly cited for the higher utilization for AC include concerns about the delay in surgery and delay in histopathological staging, patient preferences, perceived marginal benefit, and concerns about morbidity due to NAC [17, 18].…”
Section: Discussionmentioning
confidence: 99%